Tetrandrine alleviates inflammation and promotes macrophage M2 polarization in gouty arthritis by NF-κB-mediated Lcp1: The role of tetrandrine in GA - Fang, Li; Shen, Rong; Lu, Yao; Xu, Xiangfeng; Huang, Fang (Cellular and Molecular Biology, 2024)
Gouty arthritis (GA) is an inflammatory disease caused by the deposition of monosodium urate (MSU) crystals into joints. Tetrandrine (TET) is a bisbenzylisoquinoline alkaloid extracted from the root of Stephania tetrandra and can exert an anti-inflammatory function in different diseases. Nevertheless, the specific function of TET in GA remains unclear. We established the GA mouse model by MSU injection into joints of mice. Paw volume and gait score were detected for measuring the degree of joint swelling and the situation of joint dysfunction. Western blot were utilized to test the alterations of M1-related factors (IL-6, IL-1β, TNF-α, IL-12, and iNOS) and M2-related factors (Mgl1, Mgl2, Pgc1-β, Arg-1, and IL-10). The activity of NF-κB p65 in tissues was determined. The interaction of NF-κB p65 and Lcp1 was measured by ChIP and luciferase reporter assay. Lcp1 KO mice were utilized to detect the effect of Lcp1 depletion on GA process. TET treatment markedly suppressed MSU-induced joint swelling, joint dysfunction, and joint injury in GA mice. TET can also reduce inflammatory reactions in MUS-induced mice. Furthermore, we proved that TET facilitated M2 macrophage polarization and inhibited M1 macrophage polarization in GA mice. In addition, TET was found to inhibit NF-κB activity and NF-κB-mediated Lcp1 expression. Lcp1 knockdown can improve joint injury and promote M2 macrophage polarization in GA mice, while this effect was further enhanced by TET. TET alleviates inflammation and facilitates macrophage M2 polarization in GA by NF-κB-mediated Lcp1.